Grundtvigs oplysningstanker - om at knytte bånd og løse knuder - Korsgaard, Ove (Grundtvig-Studier, 2000)
Grundtvig's Educational Ideas - On tying bonds and cutting knots By Ove Korsgaard Former reseach into Grundtvig’s ideas has concentrated mostly on his pedagogical ideas and the folk high school. A third category must be added - Grundtvig’s ideas regarding enlightenment. These ideas can be understood only in the light of the main complex of problems which occupied Grundtvig throughout his entire life, namely the question: What does it imply to be a human being, a human being in society and a human being in the world? The assignment is to »develop a complete enlightenment of man«, and »human life through thousands of years«. Grundtvig wanted to establish a school system based upon two columns: the people and mankind - a folk high school and a university. We now live in the era of the school - resulting in an individualization of man which may become dangerous if there is no agreement on »the common good«. Only true enlightenment will result in the triad between the individual, the people and mankind. The folk high school was to enlighten the people. The university was to be »a spiritual workshop«, striving towards a universal understanding and towards clarification. Grundtvig’s university was never established. However, in this time of globalization the need for research into Grundtvig’s ideas of enlightenment is as great as ever.